Role of PDGF-A-Activated ERK Signaling Mediated FAK-Paxillin Interaction in Oligodendrocyte Progenitor Cell Migration - Singh, Juhi; Sharma, Kedarlal; Frost, Emma E.; Pillai, Prakash P. (Journal of molecular neuroscience, 2019)
Oligodendrocyte progenitor cells (OPCs) originate from the sub-ventricular zone of the developing brain. They migrate and proliferate to occupy the white matter tracts of the central nervous system and transform into myelinating oligodendrocytes. Along their route of migration, OPCs are guided and controlled by several growth factors and chemokines. PDGF-A (platelet-derived growth factor), a growth factor, serves as a monogenic and mitogenic cue during the process and activates intracellular signaling pathways inside the cell. Activation of extracellular signal regulated kinase (ERK) signaling is one of the mechanisms by which PDGF-A induces the migration of OPCs. However, the mechanisms governing the PDGF-A-induced ERK-driven OPCs migration are still unclear. In the current study, we investigated further the role of PDGF-A-induced ERK signaling in OPC migration. First, we confirmed the role of PDGF-A-activated ERK signaling in OPC migration using the pharmacological inhibitor U0126, or siRNA-mediated suppression of ERK expression. Then, we demonstrated that PDGF-A-induced actin reorganization and interaction of focal adhesion kinase (FAK), Paxillin, and pERK signals are impaired in OPCs treated with the MEK inhibitor U0126. Thus, our findings demonstrated that PDGF-A induces OPC migration in an ERK-dependent mechanism via regulation of actin reorganization and FAK-Paxillin interaction.